2020
DOI: 10.3727/096504019x15736439848765
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Radiosensitivity by Eurycomalactone in Human NSCLC Cells Through G2/M Cell Cycle Arrest and Delayed DNA Double-Strand Break Repair

Abstract: Radiotherapy (RT) is an important treatment for non-small cell lung cancer (NSCLC). However, the major obstacles to successful RT include the low radiosensitivity of cancer cells and the restricted radiation dose, which is given without damaging normal tissues. Therefore, the sensitizer that increases RT efficacy without dose escalation will be beneficial for NSCLC treatment. Eurycomalactone (ECL), an active quassinoid isolated from Eurycoma longifolia Jack, has been demonstrated to possess anticancer activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Understanding the underlying mechanisms by which DNA damage is repaired in cancer cells post IR treatment would facilitate overcoming RR 159 . For instance, eurycomalactone, an active quassinoid isolated from Eurycoma longifolia Jack, markedly delayed the repair of radiation-induced DSBs in non-small-cell lung cancer (NSCLC) cells 160 . Koval et al 157 reported that a protective system could be activated among cancer cells in response to IR, leading to increased resistance to subsequent exposure to IR, and moreover, chronic exposure to γ-rays increased the expression of the mus210, mus219, and mus309 genes, even after 56 days, in Canton-S flies.…”
Section: Signaling Pathways Of Ddr and Repairmentioning
confidence: 99%
“…Understanding the underlying mechanisms by which DNA damage is repaired in cancer cells post IR treatment would facilitate overcoming RR 159 . For instance, eurycomalactone, an active quassinoid isolated from Eurycoma longifolia Jack, markedly delayed the repair of radiation-induced DSBs in non-small-cell lung cancer (NSCLC) cells 160 . Koval et al 157 reported that a protective system could be activated among cancer cells in response to IR, leading to increased resistance to subsequent exposure to IR, and moreover, chronic exposure to γ-rays increased the expression of the mus210, mus219, and mus309 genes, even after 56 days, in Canton-S flies.…”
Section: Signaling Pathways Of Ddr and Repairmentioning
confidence: 99%
“…Meanwhile, the damage that occurs during G2/M can more easily cause premature entry into mitosis, which can lead to a higher possibility of passing incorrect genomic information to the next generation, or even cause mitotic catastrophe directly (43). Eurycomalactone, an active quassinoid isolated from Eurycoma longifolia, has been shown to sensitize non-small cell lung cancer cells to X-rays through a G2/M block (44). Further studies have focused on the G2/M arrest after receiving radiation.…”
Section: Cell Cycle Distributionmentioning
confidence: 99%
“…However, the mechanisms underlying the strong cytotoxicity of ECL against human NSCLC cells have not been investigated. Our previous study reported that ECL efficiently sensitized X-ray-induced apoptosis of NSCLC A549 and COR-L23 cells by inducing cell cycle arrest at the G2/M phase and inhibiting the repair of radiation-induced DNA double-strand breaks (21). Notably, ECL was also reported to inhibit the NF-κB activity in TNF-α-activated 293/NF-κB-luc cells, a stable cell line containing an NF-κB driven luciferase reporter gene (22).…”
Section: Inactivation Of Akt/nf-κb Signaling By Eurycomalactone Decrementioning
confidence: 99%